PKM PELATIHAN PENINGKATAN KETERAMPILAN BERBICARA BAHASA ARAB BAGI SANTRI PPI 259 FIRDAUS MELALUI GAME ISLAMI DI PANGALENGAN BANDUNG - Uus Rustiman; Yani Rohmayani (Indonesian Collaboration Journal of Community Services, 2023)
Learning Arabic, especially learning speaking skills (Speaking), which is applied to participants in the Arabic Language Community Islamic Boarding School PPI 259 Firdaus Pangalengan tends to be difficult and boring, so this has an effect on the slow development of participants' Arabic speaking skills (Speaking). Therefore, it is necessary to have an interesting and effective method of teaching, one of which is through games. Game (Game) is an activity that contains elements of rules, goals, and a sense of fun. There are two types of games that are usually done, namely: competitive games, in which players or teams compete to be the first to reach a goal, and cooperative games, in which players and teams work together to achieve a goal. This PKM aims to provide training to tutors for Language Institutions in the PPI 259 Firdaus Pangalengan Islamic Boarding School Area through Islamic Games to improve the English speaking skills of Language Institution participants. The aim of this training is to train tutors to teach speaking skills through Islamic games as an interesting and effective teaching method. The training participants were tutors at PPI 259 Islamic Boarding School Firdaus Pangalengan. The results of the PKM were the increase in the Arabic language skills of the PPI 259 Islamic Boarding School participants in Firdaus Pangalengan